Study of reduced self-heating effect in βGa2O3 on a different substrates utilizing SILVACO TCAD / Muhd Izhar Shahrul Anuar - Shahrul Anuar, Muhd Izhar (2020)
The architecture of high-power electronics proficient of operating at high temperatures without the need for comprehensive device heat reduction is desirable in wide sectors mainly industrial βGa2O3 is a preferable wide band gap semiconductor for having good electrical properties suitable for power applications. However βGa2O3 suffers low thermal conductivity (~0.2Wcm-1 K-1). The problem resulting in poor heat dissipation, it called self-heating effect which reduce carrier mobility and drain current degradation. Thus, the project was conducted using simulation software from SILVACO TCAD to investigate βGa2O3 fabricated on different substrates which is 4H-SiC, Silicon and βGa2O3. The structures created is to mitigate the problem to helps improve device performances. This research aim is to study the effect of reduced self¬heating effect in βGa2O3 MOSFET on different substrates utilizing SILVACO TCAD. I-V characteristic was analysed to evaluate and determine the performance of the device on various substrates helps to reduce the self-heating effect on the device. The results of the study shows that the drain current increases and slowly degrades specifically for Silicon substrates. The simulation found that 4H-SiC as hetero-epitaxial substrates helps to reduce the problem faced on βGa2O3 device by increasing origin drain current by 32.67% from 50.81mA to 67.41mA at Vg=8V. Hence, 4H-SiC is suitable substrate to increase the performance and reduce the self-heating effect of P-Ga203 substrates.